2014
DOI: 10.1523/jneurosci.3522-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis Reveals that Amyloid Precursor Protein and Death Receptor 6 Function in the Same Pathway to Control Axonal Pruning Independent of β-Secretase

Abstract: In the developing brain, initial neuronal projections are formed through extensive growth and branching of developing axons, but many branches are later pruned to sculpt the mature pattern of connections. Despite its widespread occurrence, the mechanisms controlling pruning remain incompletely characterized. Based on pharmacological and biochemical analysis in vitro and initial genetic analysis in vivo, prior studies implicated a pathway involving binding of the Amyloid Precursor Protein (APP) to Death Recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 17 publications
6
63
1
Order By: Relevance
“…Previous studies have elucidated the structures of the unbound APP extracellular domains (Wang and Ha 2004;Dahms et al 2010Dahms et al , 2012Hoopes et al 2010;Lee et al 2011; Xue et al 2011a,b;Coburger et al 2013Coburger et al , 2014. High-affinity binding of APP to death receptor 6 (DR6, also known as TNFRSF21), a death domain-containing member of the extended TNF receptor superfamily (Pan et al 1998), was recently documented (Nikolaev et al 2009) and shown to be mediated by the E2 domain of APP (Olsen et al 2014). DR6 has four cysteine-rich domain (CRD) modules in its extracellular region, followed by a transmembrane domain and death domain in its cytoplasmic region.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have elucidated the structures of the unbound APP extracellular domains (Wang and Ha 2004;Dahms et al 2010Dahms et al , 2012Hoopes et al 2010;Lee et al 2011; Xue et al 2011a,b;Coburger et al 2013Coburger et al , 2014. High-affinity binding of APP to death receptor 6 (DR6, also known as TNFRSF21), a death domain-containing member of the extended TNF receptor superfamily (Pan et al 1998), was recently documented (Nikolaev et al 2009) and shown to be mediated by the E2 domain of APP (Olsen et al 2014). DR6 has four cysteine-rich domain (CRD) modules in its extracellular region, followed by a transmembrane domain and death domain in its cytoplasmic region.…”
mentioning
confidence: 99%
“…The structure of the unbound DR6 ectodomain (ECD) (Kuester et al 2011;Ru et al 2012) revealed an elongated architecture with a kink between CRD modules 2 and 3. Genetic analysis of DR6 and APP mutant mice showed that the animals share several coincident phenotypes, including behavioral deficits, altered synapse formation, and delayed axon pruning during development or following sensory deprivation Olsen et al 2014). These and other data Olsen et al 2014) indicate that APP and DR6 function cell-autonomously and in the same pathway to stimulate axon pruning and synapse elimination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among different fragments of sAPP (Caille et al, 2004;Ohsawa et al, 1999;Olsen et al, 2014;Willem et al, 2015), the soluble Nterminal fragment (aa 18-286) and the 770 aa form sAPP(770) negatively regulate NSC growth but do not affect the number of neurospheres in the culture from acutely dissociated SVZ cells (Fig. S3).…”
Section: Resultsmentioning
confidence: 94%
“…In 2009, Genentech discovered an interaction between DR6 and amyloid precursor protein (APP), 3 a neuronal surface protein that undergoes a series of proteolytic cleavages to yield the b-amyloid (Ab) fragment. Ab aggregates form the amyloid plaques that are the hallmarks of AD and are thought to be a main upstream trigger for neurodegeneration.…”
mentioning
confidence: 99%